Comparative phylogeographic patterns in three pan-Amazonian antwren lineages (Aves: Passeriformes: Thamnophilidae: Myrmotherula and Isleria) - Chesser, R. Terry; Isler, Morton L.; Santana, Antonita; Latch, Emily K.; Stryjewski, Katherine Faust; Reed, Jennifer; Naka, Luciano N.; Fleischer, Robert C.; Aleixo, Alexandre (Zootaxa, 2025)
We examined DNA sequences of 328 individuals of three lineages (species or species complexes) of Amazonian antwrens to evaluate their degree of geographical and historical concordance. All lineages (Myrmotherula longipennis, M. menetriesii, and the Isleria guttata-hauxwelli species complex) consist of small insectivorous birds that occupy understory or midstory of terra firme forest and are widely distributed across the Amazon Basin. Individuals of each of the three lineages grouped into genetic clades mainly separated by the Amazon and some major tributaries, although members of different clades of both M. menetriesii and I. hauxwelli were documented in the Madeira-Tapajós interfluvium. Branching patterns differed among taxa, but all taxa were highly differentiated across the lower or upper Amazon. Despite the morphological, ecological, and phylogenetic similarities among lineages, and despite the fact that nearly all taxa are bounded by rivers, the effect of the other major rivers as biogeographic barriers was highly variable. The Marañón, Ucayali, Madeira, Tapajós, Xingu, Napo, Negro, and Branco all separated main clades in one or two lineages but not in the others. Levels of genetic differentiation along the Teles Pires were substantially higher than those across the Tapajós in M. menetriesii and I. hauxwelli, consistent with a proposed historical change of river course for the Tapajós. Genetic units in this study were comparable for the most part to taxonomic units delineated by analyses of vocal and morphological variation, and identical, with one exception, to units defined solely by vocal variation in a companion paper (Isler et al. 2025). These results, in conjunction with those of Isler et al. (2025), provide additional instances of the variability of responses to the historical dynamism of Amazonia, in this case in closely related and ecologically similar species; highlight the consistency of genetic differentiation with vocal differentiation in additional species of Neotropical suboscine birds; support the importance of Amazonian rivers in creating conditions that result in the differentiation of independent evolutionary lineages; and demonstrate that species richness in two of the lineages studied (M. longipennis and M. menetriesii) was previously underestimated.